Formation of Mechanisms of Investment Attractiveness in the Sphere of a Recreation and Tourism of the Region (on the Example of the Leningrad Region) - Larisa Gennadiyevna Karanatova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Now tourism represents one of the most perspective and dynamically developing branches, both world, and domestic economy. Tourism as it is noted in the Strategy of development of tourism in the Russian Federation until 2020, has to become the engine of development of regions, a link between the commercial interests of various spheres of business, priorities of state policy and cultural requirements of society. The important factor influencing social and economic develop ment of the region is increase in investment potential, decrease in risks of investors, as defines investment attractiveness both territories, and its separate branches. For many regions the sphere of a recreation and tourism plays the leading role in increase in their investment attractiveness. In the article the problem of search of mechanisms of increase in investment attractiveness of the tourist and recreational sphere at the regional level, on the example of the Leningrad Region is considered: the current state, tendencies of development of the sphere of a recreation and tourism is analyzed, problem places, points of growth come to light and the offers directed to increase in investment potential and decrease in risks of investors are formulated.